Developing user interface mobile application for tourist / Ahmad Khairul Azizi Ahmad ... [et al.] - Ahmad, Ahmad Khairul Azizi; Baharom, Shahrel Nizar; Rahaman, Ashraf Abdul; Abdullah, Muhammad; Abdul Aziz, Mohd Nasiruddin (Universiti Teknologi MARA, Perak, 2020)
Mobile phones have become full-featured mobile computers, and the usage of this technology were developed promptly. Interest towards the usages of mobile phone as an intervention in developing new application for user were also seem very promising. Much has been discus about the role of mobile application nowadays. Mobile apps that been design and created by the genius content developers, mostly are the applications that try to solve the problem facing by the user out there. Design process that has been conducted earlier in the study has led towards the invention of Thru Eye Apps. The applications are focusing on user interface and usability, and this were a baseline in developing the Thru Eyes Apps. The Thru Eye apps were developed to ease and guide tourist while traveling. With the establishment of this application, user will able to travel easily even though they travelling for the first time. Thus, this research paper discusses the user interface design process of forming Thru Eye apps in assisting tourist while travelling.